Understanding contemporary issues in higher education : contradictions, complexities and challenges - Bartram, Brendan (The Routledge Education Studies series, 2021)
"This insightful book offers a wide-ranging collection of lively discussions on contemporary issues, policies and practices in Higher Education. Bartram integrates contributions from experienced academics, teachers and students in a unique approach and structure, designed to enable students with both specific and wide-ranging interests in Higher Education to extend their understanding. Including discussion points, research tasks and suggestions on further reading in each chapter, Understanding Contemporary Issues in Higher Education discusses a range of topics, such as: Universities and the mental health 'crisis'; Knowledge, the state and the market; The role of technology in teaching and academic celebrification; Disability, diversity and inclusive placement learning. Written specifically for Education Studies students, this book constitutes a timely addition to student-focused themed studies looking at aspects of higher education"--